2013
DOI: 10.1177/1077801213517565
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Muslim and Non-Muslim Battered Immigrant Women With the Police in the United States

Abstract: Little research has been conducted to distinguish the unique experiences of specific groups of interpersonal violence victims. This is especially true in the case of battered Muslim immigrant women in the United States. This article examines battered Muslim immigrant women's experiences with intimate partner violence and their experiences with the police. Furthermore, to provide a more refined view related to battered Muslim immigrant women's situation, the article compares the latter group's experiences to ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
(54 reference statements)
1
36
0
Order By: Relevance
“…However, findings of the reviewed articles showed that researchers in Islamic countries had not investigated the relationships between religion and help seeking among Muslim women. According to findings of the studies conducted in non-Muslim-majority countries, religion’s role was mainly as an obstacle to seeking help (Ammar, Couture-Carron, Alvi, & Antonio, 2013; Kulwicki, Aswad, Carmona, & Ballout, 2010; Oyewuwo-Gassikia, 2016). Ammar, Couture-Carron, Alvi, and Antonio (2013) stated that women did not seek help because they fear the reactions from other members of the Muslim community.…”
Section: The Social Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…However, findings of the reviewed articles showed that researchers in Islamic countries had not investigated the relationships between religion and help seeking among Muslim women. According to findings of the studies conducted in non-Muslim-majority countries, religion’s role was mainly as an obstacle to seeking help (Ammar, Couture-Carron, Alvi, & Antonio, 2013; Kulwicki, Aswad, Carmona, & Ballout, 2010; Oyewuwo-Gassikia, 2016). Ammar, Couture-Carron, Alvi, and Antonio (2013) stated that women did not seek help because they fear the reactions from other members of the Muslim community.…”
Section: The Social Contextmentioning
confidence: 99%
“…According to findings of the studies conducted in non-Muslim-majority countries, religion’s role was mainly as an obstacle to seeking help (Ammar, Couture-Carron, Alvi, & Antonio, 2013; Kulwicki, Aswad, Carmona, & Ballout, 2010; Oyewuwo-Gassikia, 2016). Ammar, Couture-Carron, Alvi, and Antonio (2013) stated that women did not seek help because they fear the reactions from other members of the Muslim community. Another study by Oyewuwo-Gassikia (2016) found that the religious ideas that encouraged women to stay in abusive relationships to get a reward from God stopped women from seeking help.…”
Section: The Social Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's exposure to these barriers may be heightened by abusers' coercive and/or controlling mechanisms related to administrative status in the host countries. (This could include, for example, not filing or withdrawing required documents for granting a woman and her children regular immigration status or threatening to report a woman to officials for deportation if she calls the police) has been recognized by experts as one type of "immigration-related abuse" (Ammar, Couture-Carron, Alvi, & San Antonio, 2013).…”
mentioning
confidence: 99%
“…The literature has demonstrated that marital conflicts can appear during acculturation processes due to adjusting to the differences in new societies and the major changes in daily, family, and social life (Al-Krenawi &Graham, 2005). Ammar, Couture-Carron, Alvi, and San Antonio (2014) researched domestic violence with female Muslim immigrants and compared their results to female non-Muslim immigrants, finding out that 23% of female Muslim immigrants and 27% of female non-Muslim immigrants stated still experiencing violence from an intimate partner and the main reasons for them remaining in the relationship to be financial reasons, lack of social support, fear of the perpetrator, cultural and religious beliefs, and/or immigration-related issues (Ammar et al 2014). This study also indicated in its comparison of both Muslim and non-Muslim immigrant women, nearly 35% of the Muslim women reported cultural and religious beliefs and fear of the community's negative reactions toward divorce to be critical factors for their staying in the relationship (Ammar et al 2014).…”
Section: Partner Violence In Muslim Marriagesmentioning
confidence: 99%